2004
DOI: 10.1038/ng1354
|View full text |Cite
|
Sign up to set email alerts
|

Mutant small heat-shock protein 27 causes axonal Charcot-Marie-Tooth disease and distal hereditary motor neuropathy

Abstract: Charcot-Marie-Tooth disease (CMT) is the most common inherited neuromuscular disease and is characterized by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
506
1
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 542 publications
(525 citation statements)
references
References 30 publications
10
506
1
8
Order By: Relevance
“…Three of these mutations, R127W, S135F (one causing CMT and the other HMN) and R136W, are located in the ACD [229]. Neuronal cells transfected with the mutant Hsp27s are less viable than those expressing wildtype Hsp27 and mutation also leads to altered neurofilament assembly within cells [229].…”
Section: Mutations In the -Crystallin Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these mutations, R127W, S135F (one causing CMT and the other HMN) and R136W, are located in the ACD [229]. Neuronal cells transfected with the mutant Hsp27s are less viable than those expressing wildtype Hsp27 and mutation also leads to altered neurofilament assembly within cells [229].…”
Section: Mutations In the -Crystallin Domainmentioning
confidence: 99%
“…Neuronal cells transfected with the mutant Hsp27s are less viable than those expressing wildtype Hsp27 and mutation also leads to altered neurofilament assembly within cells [229]. Similar mutations in the ACD of Hsp22, (i.e.…”
Section: Mutations In the -Crystallin Domainmentioning
confidence: 99%
“…Furthermore, increased HSP27 levels in transgenic HSP27 mice rescue motor neurons and improve neuromuscular function following nerve injury (Sharp et al, 2006). All these studies suggest for a role of HSP27 in the pathogenesis of motor neuron degeneration.We and others identified mutations in HSP27 and its interacting partner HSP22 (small heat shock 22kDa protein 8: gene symbol HSPB8) in another motor neuron disease, distal hereditary motor neuropathy (distal HMN), supporting their pivotal role in motor neuron function Evgrafov et al, 2004;Tang et al, 2005;Kijima et al, 2005). The specific pathomechanism of these mutant small HSPs is unknown, however in vitro studies demonstrated the formation of intracellular aggregates, abnormal assembly of neurofilaments and a disturbance in axonal transport, pathological hallmarks probably triggering motor neuron death in ALS (Evgrafov et al, 2004;Ackerley et al, 2006).…”
mentioning
confidence: 59%
“…The specific pathomechanism of these mutant small HSPs is unknown, however in vitro studies demonstrated the formation of intracellular aggregates, abnormal assembly of neurofilaments and a disturbance in axonal transport, pathological hallmarks probably triggering motor neuron death in ALS (Evgrafov et al, 2004;Ackerley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation